STUDI KEBERHASILAN TANAMAN BALSA (Ochroma bicolor rowlee) DI DESA WAETELE KECAMATAN WAEAPO KABUPATEN BURU - Badrudin, Randi; Siahaya, Ludia; Tetelay, Febian (MARSEGU : Jurnal Sains dan Teknologi, 2024)
The aim of this research is to determine the success rate of Balsa plants (Ochroma bicolor rowlee) and the factors that influence the success rate of Balsa plants in Waetele Village, Waeapo District, Buru Regency. This research uses a systematic sampling method with random start, namely the first sample is created deliberately and subsequent samples are created systematically. The results of the research showed that the success rate of plants in 5 plots with the percentage of plant growth in each plot of live plants was 100% with the total growth of live plants being 100%. Meanwhile, the factors that influenced the success of Balsa plants were rainfall ranging from 1635.80 - 1977.40 mm, temperature range between 28.83°C30.44°C, air humidity range between 65.60% - 70.67%, light intensity outside the Balsa plant ranges between 853 - 965 lux, while light intensity inside the balsa plant ranges between 536 - 600 lux, soil pH in each plot/plot in the research plot ranges from 4 - 7 acid. The conclusion from this research is that the Balsa plants planted at the research location are in the successful category.